Effect of Black Sugar Cane Juice on Blood Cholesterol Levels Among Patients with Hypercholesterolemia - Ades Dewi Syafitri; Nunung Sri Mulyani (Poltekkes Kemenkes Palu, 2023)
In Indonesia, the 35.9% of population had total cholesterol levels of above the normal value, which was a combination of residents in the borderline category (total cholesterol value of 200-239mg/dl) and high category (total cholesterol value of >240mg/dl). On the other hand, 60.3% of population had LDL levels of above the normal value. Based on gender, the number of women with total cholesterol levels of above normal in was higher than men, and the number of people with total cholesterol levels of above normal in urban areas was higher than in rural areas. This study aims to determine the effect of black sugar cane juice on blood cholesterol levels among patients with hypercholesterolemia. This was a Quasi Experimental study with a pre-post test with control group design, conducted in the work area of Sapta Jaya Community Health Center, Aceh Tamiang in June 2022. The sample size of 52 people were assigned into 26 cases and 26 controls. The data collected included administration of black sugar cane juice and blood cholesterol levels. Data were analyzed using the dependent t-test and the independent t-test. Intervention was concluded to have an effect if the p value was <0.05. The dependent t-test analysis obtained mean values of blood cholesterol levels before and after administration of black sugar cane juice in the case group of 234.40 mg/dl and 201.54 mg/dl, respectively, which indicated a decrease of 32.86 mg/dl with a p-value of (0.006) <0.05. Furthermore, the independent t-test analysis in the case and control groups obtained p-values of (0.001) <0.05 and (0.003) <0.05, respectively. In conclusion, there was an effect of black sugar cane juice on blood cholesterol levels among patients with hypercholesterolemia. It is expected that patients with hypercholesterolemia consume black sugar cane juice because it can lower cholesterol levels.